Sustained Competitive Advantage Based on Industry-Specific Institutional Frameworks - Bertheussen, Bernt Arne (Frontiers in Marine Science, 2021)
This study investigates the relationships between industry-specific institutions, industry structure, and industry performance. The Norwegian Pelagic value chain’s harvesting industry and its processing industry comprised the empirical context. The study findings reveal that the harvesters (the fishers), on average, achieved nearly twice the return on assets relative to the processors. Furthermore, the fishers’ cash flow margin was, on average, more than eight times higher, and their annual growth rate was approximately 70% above the corresponding figures of the processing industry. This study argues that the two industries’ performance differences are related to the variations in their institutional setups. The processing industry is subject to the general Norwegian business environment, whereas the fish harvesting industry benefits from a sector-specific framework that supports its relative competitiveness. The fishers have collectively established a legally supported sales organization, thereby strengthening their bargaining power, vis-à-vis the processors (buyers). The fishers’ rivalry is curbed by catch share regulations, and incumbent fishers are protected from intruders through entry barriers, for example, license requirements. Moreover, the processing industry’s potential threat to vertically integrate upstream into the fish harvesting industry is blocked through legislation. Finally, in contrast to the processing industry, the fish input cost is free for the harvesting industry. This study concludes that the fish harvesting industry has gained a sustained competitive advantage over the processing industry, based on a more supportive industry-specific institutional framework.